Whose photo? Whose voice? Who listens? 'Giving, ' silencing and listening to voice in participatory visual projects. Issue 2 (3rd April 2018) - Fairey, Tiffany
Abstract : This article examines participatory visual projects that aspire to enable social change by providing communities with a platform through photography. It argues that projects are sites for negotiating rather 'giving' voice and calls for practitioners and researchers to be transparent and reflexive about these negotiated processes. Examining two sets of participant-produced images by refugee youth, one of which was shown publically and one of which went unseen, this article explores issues of control and the biases that shape editorial decisions in NGO-linked participatory visual projects. It demonstrates how voices that do not fit into dominant visual frames tend to be silenced. It is argued that this negates the critical potential of participatory visual work to enable political listening and undermines the plurality of unheard voices that participatory visual work aspires to facilitate. The article raises the central question of listening to the conception of 'voice' in participatory visual initiatives. It argues that the political and ideological promise of these projects relates not only to the voices they give rise to but to the kind of listening they enable.